Endogenous productivity of demand‐induced R&D: evidence from pharmaceuticals. (25th June 2019) - Myers, Kyle; Pauly, Mark
Abstract: We examine trends in the productivity of the pharmaceutical sector over the past three decades. Motivated by Ricardo's insight that productivity and rents are endogenous to demand when inputs are scarce, we examine the industry's aggregate Research and Development (R&D) production function. Using exogenous demand shocks to instrument investments, we find that demand growth can explain a large portion of R&D growth. Returns to scale have been stable, whereas total factor productivity has declined significantly. Predicted rents based on our estimates and Ricardo's theory closely match the trends we observe.